Prehistoric Adaptations on Fishers Island, New York: A Progress Report - Funk, R. E.; Pfeiffer, J. E. (Northeast Historical Archaeology, 1992)
Archaeological and paleoenvironmental research since 1985 on Fishers Island, New York has delineated a partially radiocarbon-dated Native American cultural sequence beginning in the Late Archaic period c. 4200 B.P. and ending at the Contact period c. A.D. 1600. Investigated settlement types included shell middens, lithic workshops, and inland hunting-gathering camps. Subsistence remains, including nuts, mollusks, and the bones of mammals, fishes, and birds indicate sporadic occupation of the island from spring through fall. Pollen recovered from both fresh water bogs and salt marshes evidence a typical postglacial forest succession beginning with the spruce-fir zone at about 13,000 B.P. and ending with the modern mixed deciduous forest.
Keywords: Archaeology; Fishers Island; New York; prehistoric adaptations